2017
DOI: 10.1038/bjc.2017.18
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes confer chemoresistance to pancreatic cancer cells by promoting ROS detoxification and miR-155-mediated suppression of key gemcitabine-metabolising enzyme, DCK

Abstract: Background:Chemoresistance is a significant clinical problem in pancreatic cancer (PC) and underlying molecular mechanisms still remain to be completely understood. Here we report a novel exosome-mediated mechanism of drug-induced acquired chemoresistance in PC cells.Methods:Differential ultracentrifugation was performed to isolate extracellular vesicles (EVs) based on their size from vehicle- or gemcitabine-treated PC cells. Extracellular vesicles size and subtypes were determined by dynamic light scattering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
208
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 229 publications
(215 citation statements)
references
References 48 publications
7
208
0
Order By: Relevance
“…The observation that heparin does not completely block this adaptive response could be because either additional non-vesicular factors are required for the response, or because some of the effects could be mediated by interaction of the EV with receptors at the cell surface without the need for EV uptake and cargo delivery. A recent study has also demonstrated that EVs released following treatment of pancreatic cancer cells with gemcitabine can induce an adaptive response in recipient cells, which may be mediated by enhanced reactive oxygen species detoxification and miR-155-induced suppression of a gemcitabine metabolising enzyme (75). Taken together, our results are consistent with the hypothesis that treatment of cells with cisplatin-EVs induces a survival mechanism that allows them to adapt to resist the effects of cisplatin.…”
Section: Cisplatin Evs Can Cause Bystander Effect and An Adaptive Ressupporting
confidence: 91%
“…The observation that heparin does not completely block this adaptive response could be because either additional non-vesicular factors are required for the response, or because some of the effects could be mediated by interaction of the EV with receptors at the cell surface without the need for EV uptake and cargo delivery. A recent study has also demonstrated that EVs released following treatment of pancreatic cancer cells with gemcitabine can induce an adaptive response in recipient cells, which may be mediated by enhanced reactive oxygen species detoxification and miR-155-induced suppression of a gemcitabine metabolising enzyme (75). Taken together, our results are consistent with the hypothesis that treatment of cells with cisplatin-EVs induces a survival mechanism that allows them to adapt to resist the effects of cisplatin.…”
Section: Cisplatin Evs Can Cause Bystander Effect and An Adaptive Ressupporting
confidence: 91%
“…18,33 Furthermore, it has also been demonstrated that their biogenesis and shedding can be influenced by extracellular stimuli, which holds broader functional significance. Although initially believed to serve as trash bags to get rid of unwanted cellular material, EVs are now established as functional entities that are capable of altering the properties of the recipient cells through transfer of bioactive cargo.…”
Section: Discussionmentioning
confidence: 99%
“…17,18,24 Since we observed an increased release of EVs under hypoxia, we evaluated if they have a role in acute survival response of pancreatic cancer cells. 17,18,24 Since we observed an increased release of EVs under hypoxia, we evaluated if they have a role in acute survival response of pancreatic cancer cells.…”
Section: Small Evs Provide the Most Survival Benefit To Cancer Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells (1×10 4 ) were grown in 96-well plates and treated with PBS or resistin (20 ng/ml) for 12 h. After treatment, cells were further treated with doxorubicin (0–2.0 μM) in presence or absence of resistin for 72 h, and cell viability was calculated using WST-1 assay kit (Roche, Indianapolis, IN), as described earlier [29, 30]. …”
Section: Methodsmentioning
confidence: 99%